MARSBOx: Fungal and Bacterial Endurance From a Balloon-Flown Analog Mission in the Stratosphere - Cortesão, Marta; Siems, Katharina; Koch, Stella; Beblo-Vranesevic, Kristina; Rabbow, Elke; Berger, Thomas; Lane, Michael; James, Leandro; Johnson, Prital; Waters, Samantha M.; Verma, Sonali D.; Smith, David J.; et al. (Frontiers in Microbiology, 2021)
Whether terrestrial life can withstand the martian environment is of paramount interest for planetary protection measures and space exploration. To understand microbial survival potential in Mars-like conditions, several fungal and bacterial samples were launched in September 2019 on a large NASA scientific balloon flight to the middle stratosphere (~ 38 km altitude) where radiation levels resembled values at the equatorial Mars surface. Fungal spores of Aspergillus niger and bacterial cells of Salinisphaera shabanensis, Staphylococcus capitis subsp. capitis, and Buttiauxella sp. MASE-IM-9 were launched inside the MARSBOx (Microbes in Atmosphere for Radiation, Survival, and Biological Outcomes Experiment) payload filled with an artificial martian atmosphere and pressure throughout the mission profile. The dried microorganisms were either exposed to full UV-VIS radiation (UV dose = 1148 kJ/m2) or were shielded from radiation. After the 5-hour stratospheric exposure, samples were assayed for survival and metabolic changes. Spores from the fungus A. niger and cells from the Gram-(-) bacterium S. shabanensis were the most resistant with a 2- and 4-log reduction, respectively. Exposed Buttiauxella sp. MASE-IM-9 were completely inactivated (both with and without UV exposure) and S. capitis subsp. capitis only survived the UV shielded experimental condition (3-log reduction). Our results underscore a wide variation in survival phenotypes of spacecraft associated microorganisms and support the hypothesis that pigmented fungi may be resistant to the martian surface if inadvertently delivered by spacecraft missions.